Правовий статус народних засідателів за радянським законодавством другої половини ХХ ст. - Лисакова, Тетяна Володимирівна; Лысакова, Татьяна Владимировна; Lysakova, Т. (My University, 2013)
In the article the questions of right status of folk assessors are examined in the soviet legal system of the second half of the ХХ century. An accent is done on the analysis of rights and duties of folk assessors in criminal procedure of this period.
Лисакова Т. В. Правовий статус народних засідателів за радянським законодавством другої половини ХХ ст. / Т. В. Лисакова // Актуальні проблеми політики : зб. наук. пр. / редкол. : С. В. Ківалов (голов. ред..), Л. І. Кормич (заст. голов. ред..), Ю. П. Аленін [та ін.] ; МОН України ; НУ ОЮА. – Одеса : Фенікс, 2013. – Вип. 48. – С. 477-485.
Keywords: радянська правова система другої половини ХХ століття; правовий статус народних засідателів в радянській правовій системі; права і обов'язки народних засідателів у кримінальному процесі радянської доби; советская правовая система второй половины ХХ века.; правой статус народных заседателей в советской правовой системе; права и обязанности народных заседателей в уголовном процессе советского периода; Soviet legal system of the second half of the twentieth century; the legal status of lay judges in the Soviet legal system; the rights and obligations of lay judges in criminal proceedings of the Soviet period